Progress in the Study of Intratumoral Microorganisms in Hepatocellular Carcinoma - Song Y; Tian S; Li Z; Miao J; Wu M; Xu T; Wu X; Qiao J; Zhang X; Zhao H; Kang L; Cao L; et al. (Journal of Hepatocellular Carcinoma)
Yagang Song,1,2 Shuo Tian,1,2 Zhanzhan Li,1,2 Jinxin Miao,1,2 Mingming Wu,1,2 Tingli Xu,1,2 Xiangxiang Wu,1,2 Jingyi Qiao,1,2 Xialei Zhang,1,3 Hui Zhao,1,2 Le Kang,1,3 Lihua Cao,1,2 Pingsheng Zhu,4 Mingsan Miao1 1Academy of Chinese Medical Sciences, Henan University of Chinese Medicine, Zhengzhou, Henan, 450046, People’s Republic of China; 2Collaborative Innovation Center of Research and Development on the Whole Industry Chain of Yu-Yao, Henan University of Chinese Medicine, Zhengzhou, Henan, 450046, People’s Republic of China; 3School of Pharmacy, Henan University of Chinese Medicine, Zhengzhou, Henan, 450046, People’s Republic of China; 4College of Chinese Medicine, Henan University of Chinese Medicine, Zhengzhou, Henan, 450046, People’s Republic of ChinaCorrespondence: Mingsan Miao, Academy of Chinese Medical Sciences, Henan University of Chinese Medicine, Zhengzhou, Henan, 450046, People’s Republic of China, Tel/Fax +86-371-65962546, Email miaomingsan@163.comAbstract: The intratumoral microbiota, an integral part of liver tumors, has garnered significant attention from researchers due to its role in tumor development regulation and impact on cancer treatment. Intratumoral microorganism not only influences tumorigenesis and progression, but also serves as potential biomarkers and targets for tumor therapy. Targeted manipulation of these microorganisms holds great promise for personalized liver cancer treatment. However, there is a lack of systematic summaries and reports on the study of intratumoral microorganism in hepatocellular carcinoma. This comprehensive review aims to address this gap by summarizing research progress related to in the field of hepatocellular carcinoma intratumoral bacteria, including their sources, types, distribution characteristics within tumors, impact on tumor development, underlying mechanisms, and application prospects. Through the analysis, it is proposed that intratumor organisms can be used as markers for liver cancer diagnosis and treatment, drug carrier materials for targeting liver cancer tissues, and the research prospects of developing new combination therapies based on the in-depth understanding of the interactions between intratumor microorganisms and the tumor microenvironment, immune cells, liver cancer cells, etc. as well as exploring the prospects of developing new combination therapies based on these interactions. It is hoped that from the perspective of intratumoral microbiota, potential theoretical support can be provided for future research on targeted cancer therapy for liver cancer intratumoral microbiota, and new insights and ideas can be provided for targeting points and research methods in tumor research.Keywords: liver cancer, intratumoral microorganisms, species and distribution, role and mechanism, development prospect